Immunotherapy of cancer tumors with inhibition of PD-1 membrane protein and its ligands interaction - A. V. Chetveryakov (Scientific Сentre for Family Health and Human Reproduction Problems, 2021)
The identification of the PD-1 receptor by Tasuku Honjo and CTLA-4 by James Ellison marked the beginning of the study of new regulatory pathways activating the immune response. The term “immune checkpoints” was introduced to denote the system of inhibitory mechanisms that include these proteins. The review presents the literature data on the molecular characteristics of the membrane protein PD-1 (programmed cell death 1 receptor) and its role in the regulation of immunity. We consider the PD-1 pathways used of by tumor cells to escape the immune response. The discovery of immune checkpoints made it possible to develop a new type of targeting therapy for cancer. The review presents the results of clinical trials of drugs that block the interaction between the PD-1 and its ligands in various types of cancer. These drugs include nivolumab, pembrolizumab, and avelumab. Studies of these drugs efficacy in patients with various types of cancer localization were conducted within the CheckMate, KEYNOTE and JAVELIN Solid Tumor programs, with some research being in progress. We analyze the results of studying the clinical efficacy of the drugs in patients with melanoma, lung cancer, renal cell cancer, colorectal cancer, classical Hodgkin’s lymphoma, Merkel carcinoma and stomach cancer. Both positive and inconclusive results in the treatment of patients are noted. These data made it possible to identify promising directions for the use of the drugs in certain localizations of the malignant process, as well as to determine the dose and time of their use to obtain an objective positive response to treatment.